The influence of age on the match-to-match variability of physical performance in women`s elite football - Baptista, I.; Winther, A. K.; Pedersen, S.; Johansen, D.; Pettersen, S. A. (Frontiers in Physiology, 2023)
Introduction: The fluctuation of external match load throughout a season is influenced by several contextual factors. While some, have been deeply analysed in men`s football literature, information is lacking on how other contextual elements, such as player`s age or experience, may affect the match-to-match variability of locomotor activities. In fact, aging has been described as a multifactorial process with the potential to affect human performance. The aim of this study is to assess if the variability of match locomotor performances fluctuates according to the players` age.